Bibliometric Analysis of Relationship Between Value Perceptions on Luxury Products Purchase Intentions Using Proquest Database - Shalihati, Fithriyyah; Hartoyo; Dewi, Febriantina (Business Review and Case Studies, 2025)
Background: The field of value perceptions and luxury product purchase intentions has experienced significant development over the past decade. The expansion of the luxury market in a given country is closely linked to prevailing luxury consumption trends. Understanding the relationship between value perceptions and purchase intentions is crucial in analyzing consumer behavior in this sector. Purpose: The objectives of this research are to analyze the chronological distribution of relevant publications, identify clustering research topics and emerging sub-themes, review the relationships between value perceptions and purchase intentions in luxury products, and propose directions for future research.Design/Methodology/approach: This study explores key themes related to value perceptions in luxury product purchasing by conducting a bibliometric analysis of 13 journal articles from the ProQuest database, utilizing VOSviewer for data visualization.Finding/Result: The findings indicate a substantial increase in research on this topic over recent years, as reflected in the growing number of studies up to 2021. Furthermore, this study confirms that purchase intention is significantly influenced by multiple factors, including value perceptions, social influence, brand prominence, price perception, and service quality. The bibliometric analysis also identified five primary research clusters, highlighting the diverse aspects of value perceptions that shape consumer intentions toward luxury product purchases.Conclusion: The results reveal 12 primary keywords and five major research keyword clusters, demonstrating that purchase intention is interconnected with all key variables, particularly value perceptions and luxury products/luxury goods. Additionally, the analysis indicates a strong and positive nexus between value perceptions and luxury purchase intentions, reinforcing the role of perceived exclusivity, prestige, and quality in shaping consumer purchasing behavior.Originality/Value (state of the art): This study also examines publication output trends, the evolution of research interest, and the network visualization of key concepts, including intention, value perception, attitude, and luxury goods. By mapping the research landscape, this study provides insights into the theoretical and practical implications of value perceptions in luxury product purchasing, contributing to the development of future research directions.Keywords: bibliometric analysis, consumer behavior, luxury product, purchase intentions, value perceptions